KUALITAS PELAYANAN TERHADAP MINAT PASIEN DALAM MEMANFAATKAN KEMBALI JASA PELAYANAN RAWAT JALAN RUMAH SAKIT DI MASA PANDEMI COVID 19: LITERATURE REVIEW - Gugun Gunawan Ahmad; Budiman Budiman; Setiawati Setiawati; Yayat Suryati; Iin Inayah; Andria Pragholapati (Jurnal Ilmu Keperawatan dan Kebidanan, 2022)
The COVID 19 pandemic currently occurring has affected hospital operations and occupancy rates. The COVID-19 pandemic affects dimensions in the quality of services provided in hospitals. Researchers are interested in conducting literature research with the title: "Assessment of service quality on patient interest in reusing Hospital outpatient services during the COVID 19 pandemic (literature review)". This study uses a literature review design with the type of narrative review. Based on the search results of research articles on journal publisher websites such as Google Scholar, Sinta Jurnal, Science Direct, DOAJ, and PubMed using keywords: "Quality of service", "Interests" "Outpatient" "Hospital" and "Covid-19 ". Of the 18 journals, only 7 research journals were included in the review. Based on the results of the literature review that researchers have done, it can be concluded that the services provided by the hospital during the COVID 19 pandemic still pay attention to the dimensions of service quality by continuing to apply the COVID 19 protocol. towards interest, considering that the reviewed journals emphasize more on aspects of patient care.Keywords: Quality of service, Interest, Outpatient, Hospital, Covid-19